Validation of Prognostic Scores for Attempted Vaginal Delivery in Scar Uterus - Soukaina, Mouiman; Oumaima, Mourran; Amina, Etber; Najia, Zeraidi; Aziz, Slaoui; Aziz, Baydada (Clinical Journal of Obstetrics and Gynecology, 2025)
Introduction: The rise in cesarean section rates globally has led to a growing population of women with uterine scars, necessitating more targeted obstetric care in subsequent pregnancies. These women are faced with the decision of attempting vaginal delivery after cesarean section (VBAC) or opting for an elective repeat cesarean section. The likelihood of a VBAC depends on various factors both maternal and fetal, gathered in two known scores Grobman and Zhang, utilizing them could make VBAC successful and more widely attempted. This study aims to validate the prognostic of these scores in a Moroccan population. Objectives: Validate the international predictive scores (Grobman and Zhang) for the probability of a successful VBAC in the Moroccan population. Explore additional criteria specific to the Moroccan population and develop a simplified VBAC score. Results: Out of 2,973 women with a cesarean history, 313 attempted TOLAC, 79% of these attempts were successful VBAC. The characteristics of successful VBAC included lower BMI, previous vaginal birth, lower estimated fetal weight, younger maternal age, and more favorable cervical conditions at admission. The Grobman and Zhang scores showed good predictive accuracy, with both models achieving 82.2% accuracy. When dividing women into groups based on predicted success (using both Grobman and Zhang scores), significant differences were found in success rates across different probability categories. Conclusion: Both Grobman and Zhang’s models were effective in predicting VBAC success in the Moroccan population, with a slight preference for the Zhang model. However, further research is needed to validate these models in clinical practice. It could involve developing a more population-specific model.